GENERAL LAW OF SIMILARITY FOR EARTHQUAKES: EVIDENCE FROM THE BAIKAL REGION - Nekrasova A.K.; Kosobokov V.G. (My University, 2006)
We have already carried out analysis of the unified scaling law for earthquakes (hereafter, USLE) both for global and several regional earthquake catalogues. In this paper, we present results of an analysis and mapping of coefficients of the USLE in the Baikal region, one of the most seismoactive regions of Russian Federation with relatively high population density.